Exploring the design and effects of internal knowledge markets - Benbya, Hind (SpringerBriefs in Digital Spaces,, 2015)
This book investigates the design and implementation of market mechanisms to explore how they can support knowledge- and innovation management within firms. The book uses a multi-method design, combining qualitative and quantitative cases with experimentation. First the book reviews traditional approaches to solving the problem as well as markets as a key mechanism for problem solving. After a short discourse on the applied methodology the book discusses internal- market types and examples of internal markets. It goes on to describe design guidelines including incentives design, governance mechanisms and lessons learned. It then analyzes the effects of internal knowledge markets. The book concludes with implications for theory and practice as well as the short-term perspectives.